The role of schools in social reconstruction: Attitudes of children, parents and teachers in Vukovar, Croatia - Čorkalo, Dinka (2004)
The experiences of post-conflict societies show that the process of trust building and normalization of social life is far slower and more demanding than the material renewal. This process is especially difficult in divided communities, as Vukovar is, where Croats and Serbs live in the same town but with practically parallel lives, and almost no mutual contacts. This division is evident in all aspects of social life, expanding also into the area of schooling. The children in Vukovar attend separate classes, divided according to the ethnicity, and the curriculum is provided either in Croatian or in Serbian language. In this way the basic condition for normalization of the intergroup relations – contact – is discouraged. Everyday, normal contact, based on reciprocity and equal status, enabling children to meet their peers from the other group and to form close relations and friendship is almost nonexistent. Following the city community for more than three years (Ajduković and Corkalo, 2002 ; 2003) we have heard from the parents of both ethnic background their worries and dissatisfaction with children being separated in schools. The present study explores in more depth the attitudes of pupils, their parents and teachers (N=1784) toward separated vs. integrated schooling and toward the variety of aspects relevant for the social reconstruction of the community in the aftermath of war. The questionnaire was administered that encompassed several aspects of attitudes toward schooling: value of education for one’ s life, attitudes toward school integration and social integration of children from different ethnic background in general, attitudes toward religious education in the schools, and attitudes toward multiculturalism. The results are discussed having in mind the complexity of issues of minority education, possibilities of school integration and the implications that such integration could have for encouraging cooperation between groups in divided community